Republic of Armenia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper on the Republic of Armenia seeks to quantify the macroeconomic impact of the government's reform agenda, which covers three broad areas: tax policy and pension; governance, government efficiency, and corruption; and labor market and competition. Strengthening growth and competitiveness and addressing governance problems requires comprehensive reform efforts. The new government has made it clear that fighting corruption and improving governance remain top priorities. Measures have been proposed to enhance corporate transparency, including through accounting and auditing reforms. A more systematic support program for small and medium-sized enterprises, along with labor market reforms, should also help alleviate unemployment difficulties. The simulations suggest that the government's tax policy reform can have a positive impact on output in the medium run if it is accompanied by supporting measures. The results suggest that a full implementation of the reform package would yield substantial benefits for the economy. In particular, it could increase real GDP by as much as 7 percent over the long run.